ASSESSMENT OF DIGITAL ICONS (Human Factors in Design, 2012)
The central question addressed in this paper is how the designer can and should ensure that the solutions are efficient and designed to meet the originally proposed goal, taking into account the user as the centerpiece of the project, after all it is for him that solutions should be designed. To provide the assessment of digital icons, this article is part of a larger research that aims to bring together methods and tools of ergonomics and usability, discuss their interactions with the main methods and tests of informational ergonomics that have been used in order to measure the comprehension of digital icons by their users, its procedures, and assessing the effects of the context of use included in each approach.